Optimalisasi Peran Orang Tua dalam Pencegahan Child Sexual Abuse Melalui Aplikasi Kance Asek - Natosba, Jum; Jaji, Jaji; Fitriani, Sukmah (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Child sexual abuse still has many unreported cases to this day because sexual abuse is still considered very inappropriate to report or publish.The increase in cases of sexual deviation, such as sexual abuse, is caused by the lack of parental awareness in protecting their children.Parents feel ashamed and do not want to talk about sex with their children because of societal taboos surrounding sex.One alternative for teaching teenagers about health and sex, including the introduction of reproductive organ names, is sex education within the family.The sexual education material on self-protection skills was developed by the community service team from various sources.The provision of sexual education, methods, and learning media needs to be considered in order to achieve the goals of sexual education.One of the methods that can be used in providing sexual education is through play-based methods.This service consists of three stages: the first stage is cadre training, the second stage is the implementation of the service by cadres to teachers and parents of students at SDN 79 Prabumulih, and the final stage is the implementation of the service by cadres to first-grade students at SDN 79 Prabumulih.The media used is the Skill Protections Learning (SPL) Program, which consists of the development of the "kance asek" application containing knowledge about preventing sexual violence for parents.The activities ran smoothly and were able to increase the parents' knowledge about the prevention of sexual violence.There is a need to disseminate information about preventing sexual violence against children in order to reduce the incidence of sexual violence against children.